Why Geographical Indications Can Support Sustainable Development in European Agri-Food Landscapes - Flinzberger, Lukas; Cebrián-Piqueras, Miguel A.; Peppler-Lisbach, Cord; Zinngrebe, Yves (Frontiers in Conservation Science, 2022)
1. Abstract Implementing the green new deal and transforming agricultural practices requires a wider and amplified policy toolbox. As many sustainability considerations are context-dependent, there is a need for instruments, which take individual characteristics of production landscapes into account. Food products with a particularly strong relationship to their landscape of origin can be marketed under the ‘Protected Designation of Origin’ label (PDO). In this article, we analyze synergies between PDO production and regional sustainable development by assessing to what extent social-ecological landscape characteristics appear in landscapes with PDO-labeled food production systems. Building upon 12 social-ecological variables we defined three landscape characteristics influential for the presence of PDOs by using a principal component analysis. Through regression models – combining those characteristics landscapes with a spatial dataset of PDO distribution in Europe – we were able to explore linkages between landscapes and products. Additionally, a geographically weighted regression delivered insights into the regional differences and product-specific relationships throughout the EU countries. Overall, we could prove the assumed positive correlation between PDO production and ecologically valuable landscapes. Further, we showed that mostly meat PDOs coincide with landscapes influenced by structural change, while cheese PDOs (despite their large number) are not well captured by our models. From the significant regression results, we conclude that PDOs can be utilized as a combined tool to support both, conservation and rural development.